Myocardial Scar and Mortality in Severe Aortic Stenosis: Data From the BSCMR Valve Consortium. Issue 18 (30th October 2018) - Musa, Tarique A.; Treibel, Thomas A.; Vassiliou, Vassiliou S.; Captur, Gabriella; Singh, Anvesha; Chin, Calvin; Dobson, Laura E.; Pica, Silvia; Loudon, Margaret; Malley, Tamir; Rigolli, Marzia; Foley, James R.J.; et al.
Abstract : Background: Aortic valve replacement (AVR) for aortic stenosis is timed primarily on the development of symptoms, but late surgery can result in irreversible myocardial dysfunction and additional risk. The aim of this study was to determine whether the presence of focal myocardial scar preoperatively was associated with long-term mortality. Methods: In a longitudinal observational outcome study, survival analysis was performed in patients with severe aortic stenosis listed for valve intervention at 6 UK cardiothoracic centers. Patients underwent preprocedural echocardiography (for valve severity assessment) and cardiovascular magnetic resonance for ventricular volumes, function and scar quantification between January 2003 and May 2015. Myocardial scar was categorized into 3 patterns (none, infarct, or noninfarct patterns) and quantified with the full width at half-maximum method as percentage of the left ventricle. All-cause mortality and cardiovascular mortality were tracked for a minimum of 2 years. Results: Six hundred seventy-four patients with severe aortic stenosis (age, 75±14 years; 63% male; aortic valve area, 0.38±0.14 cm 2 /m 2 ; mean gradient, 46±18 mm Hg; left ventricular ejection fraction, 61.0±16.7%) were included. Scar was present in 51% (18% infarct pattern, 33% noninfarct). Management was surgical AVR (n=399) or transcatheter AVR (n=275). During follow-up (median, 3.6 years), 145 patients (21.5%) died (52 after surgical AVR, 93 after transcatheter AVR). In multivariable analysis, the factors independently associated with all-cause mortality were age (hazard ratio [HR], 1.50; 95% CI, 1.11–2.04; P =0.009, scaled by epochs of 10 years), Society of Thoracic Surgeons score (HR, 1.12; 95% CI, 1.03–1.22; P =0.007), and scar presence (HR, 2.39; 95% CI, 1.40–4.05; P =0.001). Scar independently predicted all-cause (26.4% versus 12.9%; P <0.001) and cardiovascular (15.0% versus 4.8%; P <0.001) mortality, regardless of intervention (transcatheter AVR, P =0.002; surgical AVR, P =0.026 [all-cause mortality]). Every 1% increase in left ventricular myocardial scar burden was associated with 11% higher all-cause mortality hazard (HR, 1.11; 95% CI, 1.05–1.17; P <0.001) and 8% higher cardiovascular mortality hazard (HR, 1.08; 95% CI, 1.01–1.17; P <0.001). Conclusions: In patients with severe aortic stenosis, late gadolinium enhancement on cardiovascular magnetic resonance was independently associated with mortality; its presence was associated with a 2-fold higher late mortality. Abstract : Supplemental Digital Content is available in the text.